Experimental Investigation on the Effect of Casting Parameters on Thin walled Castings of Metal Matrix (LM21-SiC) Composite - L, Venkatesh; Arjunan, T.V.; Arulraj, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Â Metal matrix composites (MMCs) are widely used in several applications owing to their high strength, high specific stiffness, greater wear resistance and light weight. Normally, MMCs are processed through stir casting which exhibits poor wet ability and bonding between metal matrix and ceramic reinforcement, porosity and hot tears. These drawbacks can be overcome by squeeze casting process. Here an attempt was made on processing LM21-Sic composite for making hollow casting through squeeze casting process. Four process parameters are chosen namely squeeze pressure, stirring speed, melt temperature and reinforcement percentage. The primary objective was to experimentally investigate the influence of casting parameters on hardness & wear. Samples were cast for each experiments condition based on L9 orthogonal array. From the analysis of variance (ANOVA), it was observed that stirring speed, reinforcement percentage and Squeeze load were the process parameters making a noticeable improvement in hardness and wear. The mechanical properties such as hardness and wear are evaluated and optimum casting condition was obtained.